Dietary olive oil induces cannabinoid CB2 receptor expression in adipose tissue of Apc(Min/+) transgenic mice - Notarnicola, Maria (Nutr Healthy Aging, 2016)
BACKGROUND: Cannabinoid- 2 (CB2) receptor is known for its anti-obesity effects silencing the activated immune cells that are key drivers of metabolic syndrome and inflammation. Nutritional interventions in experimental models of carcinogenesis have been demonstrated to modulate tissue inflammation state and proliferation. OBJECTIVE: Aim of this study was to test, in Apc(Min/+) mice, whether a diet enriched with olive oil, omega- 3 and omega-6- PUFAs affects the adipose tissue inflammation status. METHODS: Four groups of animal were studied: ST group, receiving a standard diet; OO group, receiving the standard diet in which soybean oil (source of fats) was replaced with olive oil; OM-3 group, receiving the standard diet in which soybean oil was replaced with salmon oil; OM-6 group, receiving the standard diet in which soybean oil was replaced with oenothera oil. Gene and protein expression, in adipose tissue, were evaluated by RT-PCR and Western Blotting, respectively. Enzymatic activities were assayed by fluorescent and radiometric method, where appropriated. RESULTS: The diet enriched with olive oil significantly induced CB2 receptor expression and it was able to control inflammatory and proliferative activity of mice adipose tissue. CONCLUSIONS: The present findings open opportunities for developing novel nutritional strategies considering olive oil a key ingredient of a healthy dietary pattern.